Multi-level marketing in Singapore : a case study of Nu Skin. - Choo, Iris Sing Ping. (2008)
A PAPER ON THE RESEARCH DONE ON THE DEVELOPMENT OF MULTI-LEVEL MARKETING IN SINGAPORE WITH AN INSIGHT INTO NUSKIN.